An off-axis, reflective system for uniform near-field illumination in optical microscopy. (August 2018) - Ge, P; Zhang, K; Mao, L; Zhang, Y; Xu, H
In traditional optical microsopy the uniformity of off-axis illumination is poor. In this paper we propose a novel LED optical system for near-field illumination in microscopy. The system includes a LED light source, an optical collimator and a freeform, micro-reflective lens array. The Monte Carlo method is used to simulate the system. The simulation results show that the illumination uniformity can be better than 85% in the observation zone. The optical system can be put at the side of the main optical axis of the microscope. The illumination uniformity is not varied when the observation distance changes so it has good stablilty.